Endovascular therapy versus thrombolysis in patients with anterior circulation stroke in everyday clinical practice. Issue 5 (July 2016) - Kastrup, Andreas; Brunner, Freimuth; Wasser, Katrin; Hildebrandt, Helmut; Roth, Christoph; Winterhalter, Michael; Papanagiotou, Panagiotis
Background: In patients with large vessel occlusions, endovascular treatment has been shown to be superior to intravenous thrombolysis in recent trials. Aims: The aim of this study was to analyze the impact of endovascular treatment on clinical and radiological outcome in everyday clinical practice. Methods: We compared the rates of good outcome (modified Rankin scale ≤ 2 at discharge), in-hospital death, symptomatic intracranial hemorrhages, and infarct sizes in patients with distal intracranial carotid artery, M1 and M2 occlusions during two time periods. Results: From January 2008 to October 2012, a total of 509 patients were treated with intravenous thrombolysis and from November 2012 to December 2014, a total of 270 patients received endovascular treatment with stent retrievers (with or without intravenous thrombolysis). Significantly, more patients in the endovascular treatment group than in the intravenous thrombolysis group had a good outcome (37% vs. 27%, p < 0.01). The infarct sizes were significantly smaller after endovascular treatment than intravenous thrombolysis, whereas the symptomatic intracranial hemorrhages rates and in-hospital mortality were comparable between both treatment groups. The positive impact of endovascular treatment on clinical outcome was most pronounced in patients ≥75 years (31% endovascular treatment vs. 19% intravenous thrombolysis, p < 0.01), in patients with M1 occlusions (43% endovascular treatment vs. 25% intravenous thrombolysis, p < 0.01) and in patients with an admission National Institutes of Health Stroke Scale ≥ 14 (24% endovascular treatment vs. 11% intravenous thrombolysis, p < 0.05). Conclusion: In everyday clinical practice and compared with intravenous thrombolysis, endovascular treatment significantly improved clinical outcome and was associated with smaller infarctions. This beneficial effect appeared to be highest in older patients, more severely affected patients, and in those with M1 occlusions.